(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
In Ayurvedic classics use of medicinal, surgical and para surgical modalities for treatment of different ailments are given. The para surgical procedures like Agnikarma, Ksharakarma and Raktamoksan were commonly used by the Ayurvedic physicians. During the therapy like Agnikarma there were accidental burn injuries known as Pramad dagdha or Ittartha dagdha. According to nature of cause of burn it is of two types Snigdha and Ruksa. Acharya Sushruta has elaborately described the types, clinical features, treatment principles and Upadrava (complications) of Dagdha vrana. Acharya Charaka has mentioned burn wound as Agantuja vrana. Dagdha vrana (burn injury) and its management were also found in various treatise of Ayurveda written in different time periods. The paper is review of types, clinical features and management of the Dagdha vrana (burn injury) found in different ayurvedic texts.